2012
DOI: 10.1007/s10646-012-0998-9
|View full text |Cite|
|
Sign up to set email alerts
|

Chronic toxicity of tire and road wear particles to water- and sediment-dwelling organisms

Abstract: Tire and road wear particles (TRWP) consist of a complex mixture of rubber, and pavement released from tires during use on road surfaces. Subsequent transport of the TRWP into freshwater sediments has raised some concern about the potential adverse effects on aquatic organisms. Previous studies have shown some potential for toxicity for tread particles, however, toxicity studies of TRWP collected from a road simulator system revealed no acute toxicity to green algae, daphnids, or fathead minnows at concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 18 publications
4
45
0
Order By: Relevance
“…This is in agreement with previous studies evaluating the effects of TRWP mixed with sediments on aquatic organisms. 21 , 24 However, potential long-term effects caused by the slow release and gradual environmental increase of bioavailable zinc and other substances caused by aging of rubber particles are not expressed by these experiments. For G. pulex , the ingestion of car tire TP was demonstrated after a 28 day exposure to 10% car tire TP in sediment.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…This is in agreement with previous studies evaluating the effects of TRWP mixed with sediments on aquatic organisms. 21 , 24 However, potential long-term effects caused by the slow release and gradual environmental increase of bioavailable zinc and other substances caused by aging of rubber particles are not expressed by these experiments. For G. pulex , the ingestion of car tire TP was demonstrated after a 28 day exposure to 10% car tire TP in sediment.…”
Section: Resultsmentioning
confidence: 94%
“…Our results are in accordance with the findings of Panko et al, 2013, who found no significant adverse effects for benthic invertebrates H. azteca and C. dilutus after a chronic exposure to 10 g TRWP per kg of sediment dry weight. 24 In contrast, Camponelli et al 2009 showed that car tire TP with size <590 μm at 83.8 g/kg of sediment dry weight slowed down the metamorphosis of R. sylvatica larvae and zinc accumulated in their tissues. 25 Zinc content in the car tire TP mixture was roughly 0.6% in our study, in comparison to the 1.26% reported by Camponelli et al, 2009.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Over the service life of a tire, approximately 12% of the mass is released to the environment as tire and road wear particles (TRWP) produced through abrasion of the tires by roadway surfaces [6]. The potential for adverse effects to aquatic species resulting from exposure to TRWP in environmental media has been studied by various investigators [7,8,9,10,11]. With regard to human health, non-exhaust emissions, including tire and brake wear, are recognized as potential contributors to particulate matter (PM) exposure [12,13,14].…”
Section: Introductionmentioning
confidence: 99%